Center‐level CABG and valve operative outcomes and volume–outcome relationships in New York State. Issue 2 (18th December 2020) - Brooks, Cornell; Mori, Makoto; Shang, Michael; Weininger, Gabe; Raul, Sameer; Dey, Pranammya; Vallabhajosyula, Prashanth; Geirsson, Arnar
Abstract: Background: We analyzed center‐level outcome correlations between valve surgery and coronary artery bypass graft (CABG) in New York (NY) State and how volume–outcome effect differ between case types. Methods: We used the 2014–2016 NY cardiac surgery outcomes report. Center‐level observed to‐expected (observed‐to‐expected ratio [O/E]) ratio for operative mortality provided risk‐adjusted operative outcomes for isolated CABG and valve operations. Correlation coefficient characterized the concordance in center‐level outcomes in CABG and valve. Discordant outcomes were defined as having O/E ratio greater than 2 in one operation type with O/E ratio ≤1 in another. Linearized slope of volume–outcome effect in case types offered insights into centers with discordant performances between procedures. Results: Among 37 NY centers, annual center volumes were 220 ± 120 cases for CABG and 190 ± 178 cases for valve operations. Modest center‐level correlation between CABG and valve O/E ratio was shown ( R 2  = 0.31). Two centers had discordant performance between valve and CABG (O/E ≤ 1 for CABG while O/E > 2 for valve procedures). No centers had CABG O/E ratio greater than 2 while valve O/E ratio ≤1. Linearized slope describing volume–outcome effects showed stronger effect in valve operations compared to CABG: O/E ratio declined 0.1 units per 100 CABG volume increase, while O/E ratio declined 0.33 units per 100 valve volume increase. Conclusion: In NY hospitals, favorable valve outcomes may indicate good CABG outcomes but good CABG outcomes may not ensure valve outcomes. Outcome variation in valve operation could be related to stronger volume–outcome effect in valve operations relative to CABG. Valve operations may benefit from regionalization.